Antimicrobial resistance profiles of non-pathogenic Escherichia coli in pig farms in Colombia - Pabón-Rodríguez, Omar V; Buitrago-Angel, Daniela; Quintana-Moreno, Jesús D; Casas-Bedoya, Gloria A; Serna-Cock, Liliana; Torres-León, Cristian (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Antibiotic resistance is a global public health problem. So far, there are limited studies focused on Escherichia coli isolated from pig herds in Colombia. Objective: The objective of this work was to evaluate the resistance to antibiotics of non-pathogenic strains of E. coli isolated from pig farms. Methods: The hemolytic capacity and the presence of thermolabile (LT) and thermostable toxins (STa and STb) were evaluated. Finally, the resistance capacity of the strains to 11 commonly used antibiotics was evaluated in γ - hemolytic strains. Results: A total of 6 E. coli were isolated. The strains presented a high resistance capacity to antibiotics. The highest prevalence of resistance was against Amikacin (20%), Ceftiofur (20%), Fosfomycin (20%), Ciprofloxacin (40%), Gentamicin (40%), Florfenicol (80%), Enrofloxacin Baytril (80%), Norfloxacin (80%), Apramycin (100%), Ampicillin (100%) and Doxycycline (100%). Conclusions: Therefore, commensal strains of E. coli from piglets represent a high epidemiological risk to conserving and disseminating resistance genes in the pig production chain. In addition, these strains have a potential risk of presence in the food chain.